B12n12 Cluster as a Collector of Noble Gases: A Quantum Chemical Study - Cardenas-Jiron, G; Pino-Rios, R (Elsevier B.V., 2020)
Systematic analysis of the noble gas (Ng = He – Rn) trapping capacity of the B12N12 cluster were performed at the PBE0-D3/def2-TZVP level by means of thermochemical data, topological analysis of the electron density (QTAIM), non-covalent interactions index (NCI), and energy decomposition analysis (EDA). The results indicate that the Ngn@B12N12 (n = 1, 12) cluster can be obtained below room temperature. Additionally, it was found that this cluster can trap up to 12 noble gas atoms without losing stability, Finally, the effect of an applied electric field has been analysed, showing that the interaction energy can be improved through this strategy. © 2019 Elsevier B.V.